Severe Spontaneous Hematomas in Patients Hospitalized with COVID-19 - Silvia Otero-Rodriguez; Cristina Guillen; Maria Mataix; Pilar Gonzalez-de-la-Aleja; Elisabeth Cruces-Fuentes; Alix Juliette Mantilla-Pinilla; Oscar Moreno-Perez; Rosario Sanchez-Martinez; Esperanza Merino; Jose-Manuel Ramos-Rincon (International Journal of Clinical Practice)
Objective. To describe the epidemiological, clinical, laboratory, and radiological characteristics, medical treatment, and outcomes of a case series of severe spontaneous hematoma in COVID-19. Material and Methods. This retrospective study included patients hospitalized for COVID-19 who were diagnosed with severe spontaneous bleeding complications by following a standardized treatment protocol that included computed tomography angiography (CTA) from 1 March 2020 to 28 February 2022. The main outcomes were embolization and all-cause mortality. Baseline variables were analyzed for their association with mortality using bivariable logistic regression, and results were expressed as odds ratios (OR) and 95% confidence intervals (CI). Results. In total, 2450 adults were hospitalized for COVID-19 in our center during the study period. 20 patients presented severe and spontaneous intramuscular bleeding (8.1 per 1000 COVID-19 admission vs. 0.47 per 1000 non-COVID-19 admissions, p<0.001); their median age was 68.5 years (interquartile range (IQR) 63, 80), they had high comorbidity (median Charlson comorbidity index 4.5), and 95% were receiving high doses of heparin. The median interval from COVID-19 symptoms to bleeding was 17 days (IQR 13, 24), and 70% reported cough as a previous symptom. Hypovolemic shock, hypotension, and abdominal pain were the most frequent symptoms of the hematoma. All presented decreased hemoglobin, and 95% required transfusion. Intramuscular hematoma occurred most frequently in the rectus sheath, iliopsoas compartment, and femoral-iliac compartment. All patients underwent embolization; mortality was 45%. We did not identify risk factors associated with an increased risk of death. Conclusion. Although severe bleeding is an uncommon complication of COVID-19, its prevalence is higher than in inpatients without COVID-19, it usually needs embolization, and it is associated with high mortality.